Evaluation of spatial variation and nutritional status of environmental quality in the surface seawater from fishing harbours of Hainan island - Ren Bingnan; Geng Jing; Qin Dajun; Yang Bo (E3S Web of Conferences)
To investigate the nutrient distribution characteristics and the eutrophication status of the main fishing ports in Hainan Province, this study analyzed the 2021 seawater quality indicators, including biochemical oxygen demand (BOD5), chemical oxygen demand (COD), chlorophyll a (Chl a), ammonia nitrogen (NH4-N), nitrite nitrogen (NO2-N), nitrate nitrogen (NO3-N), and soluble active phosphate (DIP). The single-factor contaminant index method was employed to evaluate the water quality, revealing that the levels of COD, BOD5, and DIP surpass the national seawater quality standards for Type IV. The eutrophication index (EI) of the different fishing ports ranges from 2.38 to 56.29, indicating a high level of eutrophication.